Extent of Volunteering Work on School Vegetable Garden by Students and Teachers - Dilip, S; Thomas, Allan; Malik, Joginder Singh (Indian Journal of Extension Education, 2021)
India is the second largest producer of vegetables in the world, our productivity levels are abysmally low. Agricultural activities have produced a variety of educational benefits in primary school students. It has deepened the recognition of the importance of feeling nature, enhanced the ability of self-control and widened the understanding toward work. At disabled children's schools and in classes of disabled children, agricultural activities have immensely contributed to the development of these children, academically and socio psychologically. It is a living laboratory where lessons are drawn from real-life experiences rather than textbook examples, allowing students to become active participants in the learning process. Extent of volunteering forÂ students and teachers were measured in terms of their involvement in school vegetable gardening and wasÂ expressed as hours per week.